HUBUNGAN DISIPLIN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN KINERJA PADA PEGAWAI POLITEKNIK KESEHATAN - Novira Kurniasari (Universitas Muhammadiyah Surakarta, 2014)
In this research with the title of “The Relation of work discipline, working environment and compensation for job satisfaction on performance at Health Polytechnic Bhakti Mulia of Sukoharjo” is to know and analyze: 1) Work dicipline on job satisfaction, 2) Working environment on job satisfaction, 3) Compensation on job satisfaction, 4) Work discipline on performance, 5) Working environment on performance, 6) Compensation on performance, 7) Job satisfaction on performance. The data used was primary data taken with a list of questions given to employees of the Health Polytechnic Bhakti Mulia Sukoharjo, as many as 50 people. Analysis tool used that includes test the validity of using the technique of one-shot method with SPSS and reliability testing using the technique of Cronbach’s alpha, testing the hypothesis include F-test, the coefﬁcient of determination (R2), correlation analysis, the effect of direct, the effect of indirect and total effect. The test results showed all variables are valid and reliable. From the results of the analysis obtained the following that: 1) This is tested in the same time that work discipline variable, work environment, compensation and job satisfaction give inﬂuence to the work performance, 2) Effect of R2 Square of 0.687 or 69%, this means that performance, explained by the work discipline, working environment and compensation with job satisfaction as an intervening variable of 69%.